De liefde van God - Muis, Jan (Nederduitse Gereformeerde Teologiese Tydskrif, 2012)
The love of God In this essay, an attempt is made to understand what Christians mean by the love of God. Starting point for this understanding is the biblical witness about the decisive self-revealing actions of love God has performed in the history of Israel and in Jesus Christ. Then, different forms of human love are described. A definition of divine love is given in terms of elements that can be found in these forms of human love and in God’s self-revealing actions of love. Two questions about this definition that are crucial to Vincent Brümmer’s account of the love of God, are discussed. First, what is the nature of God’s longing? And second, does the love between God and human beings exclude rights and duties?